THE PROFILE OF MULTIPLE SCLEROSIS IN GENERAL PRACTICE. Issue 11 (14th October 2015) - Binks, Sophie; Green, Liz
Abstract : Introduction: Multiple sclerosis (MS) is a long-term neurological condition requiring a multi-disciplinary team approach. Recently, NICE highlighted the role of primary care professionals in MS management through an updated clinical guideline. This quality improvement project investigated aspects of MS patient care in a large Brighton GP practice. Method: Electronic GP records were searched to identify all currently registered patients with a diagnosis of MS. Details of initial presentation, epidemiology and care received over a one-year period were examined. Results: There were 19 patients, representing a prevalence of 186 per 100, 000. Most patients first presented in GP with sensory disturbance, optic neuritis or motor symptoms. The mean number of primary care contacts per patient per year was 4.3, compared to 0.4 contacts per person per year with a neurologist and 0.5 with the MS nurse. 46% of GP consultations were wholly or partially related to the patient's MS. Around half of patients took up proactive interventions such as flu vaccination (47%) and Vitamin D monitoring (50%). Conclusions: Primary care professionals are significant contributors to the care of people with MS with frequent patient contact. During this project, patients were reminded of preventive care opportunities and this will be re-audited in 2015.